2020
DOI: 10.1080/22221751.2020.1757388
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin is essential for the entry of Japanese encephalitis virus into the human brain microvascular endothelial cells

Abstract: Japanese encephalitis virus (JEV) remains the predominant cause of viral encephalitis worldwide. It reaches the central nervous system upon crossing the blood-brain barrier through pathogenic mechanisms that are not completely understood. Here, using a high-throughput siRNA screening assay combined with verification experiments, we found that JEV enters the primary human brain microvascular endothelial cells (HBMEC) through a caveolae-mediated endocytic pathway. The role of ezrin, an essential host factor for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…In vitro experiments have confirmed that some flaviviruses can infect and replicate in BMECs in vertebrates. 36 , 37 However, the infection and replication of flavivirus in BMECs of human patients still lack sufficient direct evidence and require histological confirmation. ZIKV persistently infects and continuously replicates in primary hBMECs in vitro , without obvious cytopathology or increased endothelial cell permeability.…”
Section: How Do Endothelial Cells Of the Bbb Respond To Viral Infectimentioning
confidence: 99%
“…In vitro experiments have confirmed that some flaviviruses can infect and replicate in BMECs in vertebrates. 36 , 37 However, the infection and replication of flavivirus in BMECs of human patients still lack sufficient direct evidence and require histological confirmation. ZIKV persistently infects and continuously replicates in primary hBMECs in vitro , without obvious cytopathology or increased endothelial cell permeability.…”
Section: How Do Endothelial Cells Of the Bbb Respond To Viral Infectimentioning
confidence: 99%
“…ATP6V1A directly interacts with rabies viral matrix protein facilitating uncoating [52]. EZR is an essential host factor required for the entry of [21] Japanese encephalitis virus into human brain microvascular endothelial cells [53]. HSPA9 has been identified as a putative receptor for Tembusu virus [54].…”
Section: Discussionmentioning
confidence: 99%
“…As described in previous studies, 12 HBMECs (2 × 10 4 cells/well) were seeded on a collagen‐coated 96‐well black optical base plate (Nunc; Thermo Fisher Scientific). The cells (70% confluence) were then transfected with 75 nM siRNA and incubated for 60 h. After 48 h of infection with EV71 at a multiplicity of infection (MOI) of five, the cells were fixed and immunofluorescence was then used to analyze the expression of EV71 capsid VP1.…”
Section: Methodsmentioning
confidence: 99%